MICROCLIMATIC VARIATIONS IN SURROUNDING OF TWO PUBLIC SCHOOLS IN THE CITY OF CUIABÁ/MT - França, Mauro Sergio de; Maitelli, Gilda Tomasini; Nogueira, Marta Cristina de Jesus Albuquerque (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
The city of Cuiabá, located in the tropical and central South America, stands out on the national stage by high temperatures throughout the year and by the accelerated growth in recent decades, causing the expansion of its perimeter and development of urban activities that caused climate evidenced by several studies. This study aimed to compare the microclimatic variables with land use in the vicinity of two public schools in Cuiabá / MT. The methodology was based on data collected daily and hourly temperature and relative humidity for one year (February 2011 to January 2012), obtained with the aid of automatic weather stations fixed, installed in the state school Padre Ernesto Camilo Barreto municipal and school Our Lady of Aparecida. The results showed microclimatic differences between the two areas, and the values recorded in the most built, the school environs Padre Ernesto, presented in most times at higher temperatures compared with observed data in the area farthest from the central portion, and the surroundings school Our Lady of Aparecida. It was found that the use of soil in different urban areas causes different microclimates.